Concentration and seasonal variation of Be-10 in surface aerosols of Lhasa, Tibet - Huang Jie; Kang ShiChang; Shen ChengDe; Cong ZhiYuan; Liu KeXin; Wang Wei; Liu LiChao (Chinese Science Bulletin, 2010)
Thirty samples of total suspended particles were collected at a site in western part of Lhasa, Tibet from August 2006 to July 2007. The Be-10 concentrations were determined by Accelerator Mass Spectrometer (AMS). Analysis of correlation between Be-10 concentrations and meteorological factors revealed that the wet scavenging has little effect on Be-10. Be-10 can be used as a proxy of transport processes of the upper atmosphere over the Tibetan Plateau. Analysis of correlation between Be-10 concentrations and NCEP reanalysis data demonstrated that higher Be-10 concentrations in spring were probably caused by the atmosphere exchange from stratosphere to troposphere during February to June. Lower Be-10 concentrations during August to September were consistent with the synchronous lower O-3 values, suggestive of both Be-10 and O-3 were probably influenced by the atmosphere exchange from troposphere to stratosphere. Multidisciplinary Sciences SCI(E) 0 ARTICLE 23 2572-2578 55